A Predictive Input Shaping Control for Swing Suppression of an Overhead Crane System Subjected to Non-Zero Initial Condition and Payload Hoisting - Aina Syazwin Binti Mohd Shukor (Universiti Sains Islam Malaysia, 2025)
Matric: 3231291 (FKAB)-Restricted until May 2028